(untitled) (Italian Journal of Public Health, 2006)
Genetic testing has moved rapidly from research to clinical use and the issues of quality have not always received sufficient attention. In response to these needs to improve the overall quality assurance system for genetic testing and services there have been several international initiatives that are reviewed here. The main activities at European level towards improving the quality assurance of genetic testing are described.